(untitled) (Journal of Statistics on Health Decision, 2022)
A recent study by our team suggested that interventions based on pain neuroscience education and exercise are similarly effective in the treatment of adolescents with neck pain (NP). However, we were unable to find any studies that explored factors of treatment response. Thus, this study aimed to explore whether sociodemographic data, pain characteristics, psychosocial factors, sleep, symptoms of central sensitization, pressure pain thresholds and neck muscles endurance at baseline predicted clinical improvement when using different standards: the Patient Global Impression of Change (PGIC) scale and the minimal change in the Numeric Pain Rating Scale (NPRS) for pain intensity and the Functional Disability Inventory (FDI) for disability, at post-intervention and 6-month follow-up. This study is a secondary analysis of a randomized controlled trial conducted with 127 adolescents with NP. To classify adolescents who improved, clinical improvement criteria were used: i) reporting a PGIC≥5 (moderately better, better, or a great deal better), ii) ≥50% reduction of pain intensity in the NPRS, iii) ≥50% reduction of disability in the FDI, and iv) ≥50% reduction in the NPRS and in the FDI, from baseline levels. Independent logistic-regression analyses were used to examine univariable and multivariable associations between the independent and dependent (clinical improvement) variables. At post-intervention, a multivariable model was found for the improvement of 50% in the FDI in which older age (OR=0.64, p<0.05) and moderate physical activity (OR=1.00, p<0.05) remained associated with decreased and increased likelihood of improvement, respectively. At 6-month follow-up, two multivariable model were found for the improvement of 50% in the NPRS in which higher disability (OR=0.94, p<0.05) remained associated with decreased likelihood of improvement and for the improvement of 50% in the FDI in which having pain often (OR=0.23, p<0.05) and higher neck flexors endurance (OR=1.07, p<0.05) were associated with decreased and increased likelihood of improvement, respectively.